Aristolochic acid I exposure decreases oocyte quality - Li, Weidong; Zhang, Jiaming; Yu, Xiaoxia; Meng, Fei; Huang, Ju; Zhang, Liangran; Wang, Shunxin (Frontiers in Cell and Developmental Biology, 2022)
Oocyte quality is a determinant of a successful pregnancy. The final step of oocyte development is oocyte maturation, which is susceptible to environmental exposures. Aristolochic acids (AAs), widely existing in Aristolochia and Asarum plants that have been used in traditional medicine, can result in a smaller ovary and fewer superovulated oocytes after in vivo exposure to mice. However, whether AAs affect oocyte maturation and the underlying mechanism(s) are unclear. In this study, we focused on the effect of Aristolochic acid I (AAI), a major compound of AAs, on the maturation of in vitro cultured mouse oocytes. We showed that AAI exposure significantly decreased oocyte quality, including elevated aneuploidy, accompanied by aberrant chiasma patterns and spindle organization, and decreased first polar body extrusion and fertilization capability. Moreover, embryo development potential was also dramatically decreased. Further analyses revealed that AAI exposure significantly decreased mitochondrial membrane potential and ATP synthesis and increased the level of reactive oxygen species (ROS), implying impaired mitochondrial function. Insufficient ATP supply can cause aberrant spindle assembly and excessive ROS can cause premature loss of sister chromatid cohesion and thus alterations in chiasma patterns. Both aberrant spindles and changed chiasma patterns can contribute to chromosome misalignment and thus aneuploidy. Therefore, AAI exposure decreases oocyte quality probably via impairing mitochondrial function.